Accidentswith biological material involving clinical analysis laboratory professionals - Prado-Palos, Marinésia A; Canini, Silvia RMS; Gir, Elucir; Melo, Lílian L; Mata, Daniela H; Santana, Raide MT; Souza, Lorena R; Souza, Adenícia CS (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: the risk of exposure to biological material in clinical analysis laboratories is high, due to the constant manipulation of organic fluids and blood.Objective: identify the frequency and main causes of occupational accidents with biological material among professionals that work in clinical analysislaboratories. Methods: this descriptive study was conducted in clinical analysis laboratories at two teaching hospitals in Goiânia/GO, Brazil. Results:considering 81 professionals interviewed, 9 (11,1%) had not been vaccinated against hepatitis B; 45 (55,5%) referred accident with biological material; being36 (80%) exposed to percutaneous injuries and 9 (20%) to mouth and ocular mucosa splashes; 22 (48,9%) subjects did not notify any accidents, and one workerwas infected by the hepatitis B virus after the accident. The main causes attributed to accident occurrence included inadequate or lack of personal protectiveequipment, work overload, self confidence and insufficient piercing and cutting material collectors. Conclusion: the high prevalence of accidents, allied toinsufficient notification, can cause serious damage to professionals and institutions. This deserves urgent efforts to implement an accident prevention and healthpromotion program.